Use of fresh and preserved bovine amnion in urinary bladder reconstruction in goats : Gross histopathological and histochemical study - REDDY, C V; GUPTA, O P; CHARAN, K; SINGH, G R (The Indian Journal of Animal Sciences, 2012)
Subtotal cystectomy performed in 18 animals was reconstructed by fresh bovine amnion in group 1, frozen and boiled amnion in group 2 and 1% geutaraldehyde-treated amnion in group 3. These amnion grafts werc covered by newly regenerated bladder tissue by day 30 and 60 after amniocystoplasy. Replacement regenerated bladder tissue completed in groups 1 and 2, whereas the graft was detached after regeneration in group 3. There was partial and complete covering of regenerated bladder tissue on days 30 and 60, respectively, in all groups, but in group 3 the epithelia regeneration was less. Deposition of collagen and elastic fibres was more uniform and organized appropriately at day 60 in all the group. Fresh amnion and amnion preserved by freezing and subsequent boiling and 1% gtuturaldchyde treated elicited immunological response.